2001
DOI: 10.1007/s004670000486
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of proteinuria in children using the urinary protein-osmolality ratio

Abstract: A prospective study was conducted to determine the correlation of early morning urinary protein/osmolality ratio (mg/l/mosmol/kg) with 24-h urinary protein excretion (mg/m2/day). Study patients consisted of 53 children (aged 1 month to 15 years). Early morning urine samples and 24-h urine samples were collected and analyzed. In group 1 (children without proteinuria), early morning urinary protein/creatinine ratio (Uprot/Ucr, mg/mg) was 0.061 +/- 0.011 and the protein/osmolality ratio (Uprot/Uosm, mg/l/mosmol/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…The performance and validity of urine osmolality adjustment in environmental biomonitoring has not been evaluated, although a few studies have supported that albumin-to-osmolality ratio or protein-to-osmolality ratio correlates closely with 24-hour measurements (Gyamlani et al, 2003; Kim et al, 2001; Morgenstern et al, 2003). In our study, we found that the variation in urine osmolality related to socio-demographic background and medical conditions was less dramatic compared to urine creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…The performance and validity of urine osmolality adjustment in environmental biomonitoring has not been evaluated, although a few studies have supported that albumin-to-osmolality ratio or protein-to-osmolality ratio correlates closely with 24-hour measurements (Gyamlani et al, 2003; Kim et al, 2001; Morgenstern et al, 2003). In our study, we found that the variation in urine osmolality related to socio-demographic background and medical conditions was less dramatic compared to urine creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting these specimens accurately is difficult and time consuming, especially in infants and in patients suffering from incontinency or enuresis. Ratios of protein to osmolality 5 , 6 and protein to creatinine in single-voided urine specimens have been offered as appropriate tools for assessing urinary protein. 4 , 7 , 8 , 9 Urinary excretion of creatinine may vary in newborns 10 and spot urine may be influenced by the hydration-dehydration condition of patients.…”
mentioning
confidence: 99%
“…Wilson et al reported in an adult study that the ratio of 0.12 of Uprot/Uosm was coincident with proteinuria with sensitivity 96% and specificity 93% by ROC curve method [8]. The cut-off value of Uprot/ Uosm ratio was 2.5 mg/l/mOsm/kg for estimating nephrotic proteinuria ([3 g/days) and correlation coefficient between Uprot/Uosm ratio and 24-h protein excretion was 0.88 in this study.…”
Section: Discussionmentioning
confidence: 82%